Is lifestyle a determining factor for body satisfaction in high education? - Nascimento Junior, José Roberto Andrade do; Moreira, Caio Rosas; Gonçalves, Marina Pereira; Bezerra, Thaynã Alves; Souza Filho, Anastacio Neco de; Fiorese, Lenamar; Carvalho, Ferdinando Oliveira (Cuadernos de Psicología del Deporte, 2019)
People’s lives are increasingly hurrying because of several factors that interfere with lifestyle. However, little is known how much this style interferes in people body satisfaction. This study investigated the impact of lifestyle on body satisfaction of the university community. A total of 659 students (n=460), professors (n=49) and administrative staff (n=150) of a federal northeastern Brazilian university, answered the Body Satisfaction Situational Scale and Fantastic Lifestyle Questionnaire. Linear regression indicated that the work has a positive impact on the satisfaction of external parties for students, while for the administrative staff was the lowest alcohol consumption and being with family/friends that the impact, as professors, body satisfaction suffered impact of higher alcohol consumption, aggressive behavior, sleep deprivation, lower stress management and unsafe attitudes (p < .05). It is concluded that the lifestyle profile can be considered a determining factor for body satisfaction in higher education, contributing or not for higher body satisfaction.